Learning from Japan: Advancing Education in the Arab and Islamic World through Creative Approaches - Habib Badawi (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2023)
Taking a historiographical approach, this research delves into Japan's history, culture, and education. It aims to uncover the key curricular reforms and societal influences that have contributed to its academic excellence. This study highlights Japan's exceptional academic leadership. It traces it back to historical milestones, academic reforms, societal attitudes, and cultural frameworks. Notably, the Japanese educational model emphasizes principles such as effort, collaboration, problem-solving, and comprehensive education, which have played a significant role in their success. By drawing inspiration from these findings, school policymakers, practitioners, and stakeholders in the Arab and Islamic worlds can consider adopting and adapting elements of the Japanese educational model. This will inform curricular reforms and foster academic excellence. Moreover, this study recognizes the importance of fostering a collaborative exchange of ideas and experiences between Japan and the Arab and Islamic worlds. By embracing Japan's historical lessons and engaging in transformative dialogues, both regions can shape the future of education, promoting deeper understanding and more effective policies. However, it is imperative to acknowledge the limitations of this study, such as the limited sample size, cases, and variations. Therefore, further research is warranted to explore more diverse cases, larger sample sizes, and varied demographics. This will enable us to attain a deeper and more comprehensive understanding that can guide the formulation of appropriate and effective educational policies.